2011
DOI: 10.1007/s10826-011-9469-9
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Clinical, and Geographic Predictors of Placement Disruption among Foster Care Youth Receiving Wraparound Services

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 35 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…This aligns with Cox et al's (2010) and Weiner et al's (2011) findings that natural supports, community resources, and child strengths were influential in leading to positive outcomes for youth in wraparound. Results provide further evidence for the theory that focusing on an individual's strengths is connected to enhanced well-being (Wood et al, 2011), and adds further empirical support for using a strengths-based approach within community-based mental health services (Bruns et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This aligns with Cox et al's (2010) and Weiner et al's (2011) findings that natural supports, community resources, and child strengths were influential in leading to positive outcomes for youth in wraparound. Results provide further evidence for the theory that focusing on an individual's strengths is connected to enhanced well-being (Wood et al, 2011), and adds further empirical support for using a strengths-based approach within community-based mental health services (Bruns et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Weiner, Leon, and Stiehl (2011) collected information about child protective factors (e.g., positive relationships with family, positive relationships with peers, coping skills) using the Child and Adolescent Needs and Strengths tool (CANS; Lyons, 2009). Results revealed that a higher score for child strengths predicted greater placement stability (Weiner et al, 2011).…”
Section: Individual Protective Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may suggest that caregiver and child services are required concurrently, or that family treatment is a necessary additional component to caregiver service use (Mears et al 2009). These wraparound services, however, may be unavailable to families who live in communities characterized by poverty and adverse conditions (Weiner et al 2011). In particular, in the current study, higher quality, wraparound services may have been inaccessible to the caregivers in the sample, and may partially explain the unexpected exacerbating effect of caregiver service utilization on child externalizing problems.…”
Section: Implications For Practice Policy and Future Researchmentioning
confidence: 73%
“…Proactively providing these children with intensive trauma-related services at the outset of their OOHC episode may reduce the risks of poor service outcomes that are associated with complex traumatization such as placement disruption (Weiner, Leon, & Stiehl, 2011) or psychiatric hospitalizations . Likewise, additional research should focus specifically on the treatment trajectories of this particularly vulnerable subgroup to identify those placement settings wherein these youth are most successful.…”
Section: Trauma Exposure and Trauma-related Symptomsmentioning
confidence: 99%